Slim: OS Kernel Support for a Low-Overhead Container Overlay Network - Zhuo, Danyang; Zhang, Kaiyuan; Zhu, Yibo; Liu, Hongqiang Harry; Rockett, Matthew; Krishnamurthy, Arvind; Anderson, Thomas (16th USENIX Symposium on Networked Systems Design and Implementation (NSDI '19), 2019)
Containers have become the de facto method for hosting large-scale distributed applications. Container overlay networks are essential to providing portability for containers, yet they impose significant overhead in terms of throughput, latency, and CPU utilization. The key problem is a reliance on packet transformation to implement network virtualization. As a result, each packet has to traverse the network stack twice in both the sender and the receiver’s host OS kernel. We have designed and implemented Slim, a low-overhead container overlay network that implements network virtualization by manipulating connection-level metadata. Our solution maintains compatibility with today’s containerized applications. Evaluation results show that Slim improves the throughput of an in-memory key-value store by 66% while reducing the latency by 42%. Slim reduces the CPU utilization of the in-memory key-value store by 54%. Slim also reduces the CPU utilization of a web server by 28%-40%, a database server by 25%, and a stream processing framework by 11%.